Systematik zur technologie-induzierten Produkt- und Technologieplanung - Wall, Marina

Systematik zur lösungsmusterbasierten Entwicklung von Frugal Innovations - Lehner, Anne-Christin

Methodik zur Bewertung von Produktionssystemen in der frühen Entwicklungsphase - Rudtsch, Vinzent

Ernährung und psychische Erkrankungen - Libuda, Lars; Antel, J.; Hebebrand, J.; Föcker, M. (Der Nervenarzt)

Strategische Produkt- und Prozessplanung - Gausemeier, Jürgen; Echterfeld, Julian; Amshoff, Benjamin (Handbuch Produktentwicklung)

Systematik zur musterbasierten Entwicklung technologie-induzierter Geschäftsmodelle - Amshoff, Benjamin

Außerschulische Nutzung neuer Technologien durch Jugendliche und der Zusammenhang mit dem Erwerb computer- und informationsbezogener Kompetenzen - Vennemann, Mario; Eickelmann, Birgit; Drossel, Kerstin; Bos, Wilfried (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

Gelingensbedingungen IT-bezogener Lehrerkooperation als Merkmal von Schulqualität - Drossel, Kerstin; Schulz-Zander, Renate; Lorenz, Ramona; Eickelmann, Birgit (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

Vertiefende Analysen zu ICILS 2013 – Befunde und mögliche Entwicklungsperspektiven - Eickelmann, Birgit; Gerick, Julia; Drossel, Kerstin; Bos, Wilfried (ICILS 2013. Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

ICILS 2013. Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen

Der Sozialindex: Theoretische Fundierung und forschungspraktische Relevanz für die Erfassung der Schülerkomposition von Gymnasien - Becker, Dominik; Drossel, Kerstin; Schwanenberg, Jasmin; Wendt, Heike; Bos, Wilfried (Sozialindices für Schulen. Hintergründe, Methoden und Anwendung)

Alterung spritzgegossener thermoplastischer Mikrobauteile - Meister, Steve

Einfluss der Nanopartikelgeometrie auf ie Buchzähigkeit und das Ermüdungsrissausbreitungsverhalten von Epoxidharzen - Kothmann , Martin H.

Rheologische und verarbeitungstechnische Eigenscahften von reaktiv prozessierten Polethelnterephthalaten - Härth , Michael

Der Einfluss stoffschlüssiger Fügeverfahren auf die Verbundfestigkeit flammgeschützter Kunststoffe - Evers , Fabian

Berechnung und Simulation von Feststoffförderprozesse in Einschneckenextrudern bis in den Hochgeschwindigkeitsbereich - Leßmann , Sebastian

Prozessphasenoptimierte Simulation und Modellierung des Spritzgießsonderverfahrens GITBlow - Seidel, Stefan

Entwicklung und Validierung konstruktiver Merkmale bei thermoplastischen Kunststoffblindverschraubungen mit dichtendem Hinterschnitt - Krugmann , Jens

Verarbeitung von PET auf gleichläufigen Doppelschneckenextrudern - Herken , Tobias

Ein Beitrag zur Veränderung der Kunststoffoberfläche durch Atmosphärendruck-Plasma - Leister , Christian

Relevance of Morning and Evening Energy and Macronutrient Intake during Childhood for Body Composition in Early Adolescence - Diederichs, Tanja; Roßbach, Sarah; Herder, Christian; Alexy, Ute; Buyken, Anette (Nutrients)

Wie verhalten sich Aktionäre bei Unternehmenszusammenschlüssen? Modellierung sprachlicher Muster zur Analyse treibender Faktoren bei der Berichterstattung - Stotz, Sophia; Geierhos, Michaela (DHd 2016: Modellierung - Vernetzung - Visualisierung. Die Digital Humanities als fächerübergreifendes Forschungsparadigma. Konferenzabstracts, Universität Leipzig, 7. bis 12. März 2016)
Welche Informationen über Unternehmenszusammenschlüsse werden in Zeitungsnachrichten vermittelt, und wie können diese Informationen automatisch extrahiert werden? Dies soll am Beispiel des Verhaltens von Aktionären während eines Zusammenschlusses ermittelt werden. Dazu werden die wichtigsten Aussagen über das Votum der Aktionäre im Hinblick auf eine automatische Erkennung sprachlich analysiert. Im Fokus stehen dabei die Berichte über Aktionärsabstimmungen hinsichtlich der Annahme bzw. Ablehnung eines Übernahmeangebots.

Webmonitoring - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Webmonitoring

Sentimentanalyse - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Sentimentanalyse

Text Mining - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Text Mining

Crawler (fokussiert / nicht fokussiert) - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Crawler

Influence of the Surface and Heat Treatment on the Bond Strength of Galvanized Steel/Aluminum Composites Joined by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Grothe, Richard; Schmidt, Hans Christian; Hordych, Illia; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
The influence of a chemical or mechanical surface modification followed by different post-heat treatments on the bond strength of galvanized steel/ aluminum composites is studied. An incremental rolling process is used for joint formation based on plastic deformation. The morphology, the chemical state of the modified surfaces as well as the cross-section, and local potential distribution of the welded zone is characterized by different microscopic and spectroscopic methods. The stability of the joint is analyzed by a shear-force test in combination with microscopic failure analysis. A clear correlation between pre/post-treatment and the joint strength is observed.

Molecular Engineering of Aluminum-Copper Interfaces for Joining by Plastic Deformation - Hoppe, Christian; Ebbert, Christoph; Voigt, Markus; Schmidt, Hans Christian; Rodman, Dmytro; Homberg, Werner; Maier, Hans Juergen; Grundmeier, Guido (ADVANCED ENGINEERING MATERIALS)
Interface modification based on ultra-thin mercapto-propyl(trimethoxy) silane (MPTMS) films is shown to promote joining of copper and aluminum by plastic deformation followed by a heat treatment. The surface morphology and the surface chemistry of the metal substrates were analyzed by means of FE-SEM, XPS, and FT-IRRAS. The spectroscopic data show that the MPTMS film is crosslinked via Si-O-Si bonds and that stable Cu-S and Si-O-Al interfacial bonds are formed. The shear-force tests of the joints led to force displacement curves that are characteristic for a covalently bonded interface. Complementary cross sectional SEM and EDS analysis of the joint proved that a defect-free interface was formed without any measureable interdiffusion of metals across the interface or cracking of an oxide films.

Congestion Games with Mixed Objectives - Leder, Lennart

A versatile design for resonant guided-wave parametric down-conversion sources for quantum repeaters - Brecht, Benjamin; Luo, Kai-Hong; Herrmann, Harald; Silberhorn, Christine (Applied Physics B)

On-chip generation of photon-triplet states - Krapick, Stephan; Brecht, Benjamin; Herrmann, Harald; Quiring, Viktor; Silberhorn, Christine (Optics Express)

The FiESTA data model: a novel approach to the representation of heterogeneous multimodal interaction data - Menke, Peter

Competition of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen (Theoretical Economics Letters)
On an intermediate goods market with asymmetric production technologies as well as vertical and horizontal product differentiation we analyze the influence of simultaneous competition for resources and customers. The intermediaries face either price or quantity competition on the output market and a monopolistic, strategically acting supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Moreover, the well-known welfare advantage of price competition can in general be no longer confirmed in our model with an endogenous input market and asymmetric intermediaries.

Competition in Markets with Intermediaries - Manegold, Jochen

Comparison of different Definitions of Chosen-Ciphertext Security in Encryption schemes - Porzenheim, Laurens

Geodaten in Social Media als Informationsquelle in Krisensituationen - Mirbabaie, Milad; Tschampel, N.; Stieglitz, Stefan (Proceedings of the 9th Multikonferenz Wirtschaftsinformatik)

Volunteered Geographic Information and its Implications for Disaster Management - Mirbabaie, Milad; Stieglitz, Stefan; Volkeri, S. (Proceedings of the 49th Hawaii International Conference on System Sciences)

Commitment Schemes - Definitions, Variants, and Security - Bemmann, Kai Sören

Experimentelle und numerische Untersuchungen des Crashverhaltens hybridgefügter Verbindungen - Hein, David; Meschut, Gerson; Matzenmiller, Anton; Nelson, Alexander (16. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Werkstoffgerechte Fügetechnologien als Schlüssel für innovative Mischbauweisen - Hein, David; Meschut, Gerson (Anwendertreff Leichtbau)

Churn- and DoS-resistant Overlay Networks Based on Network Reconfiguration - Drees, Maximilian; Gmyr, Robert; Scheideler, Christian (Proceedings of the 28th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We present three robust overlay networks: First, we present a network that organizes the nodes into an expander and is resistant to even massive adversarial churn. Second, we develop a network based on the hypercube that maintains connectivity under adversarial DoS-attacks. For the DoS-attacks we use the notion of a Omega(log log n)-late adversary which only has access to topological information that is at least Omega(log log n) rounds old. Finally, we develop a network that combines both churn- and DoS-resistance. The networks gain their robustness through constant network reconfiguration, i.e., the topology of the networks changes constantly. Our reconguration algorithms are based on node sampling primitives for expanders and hypercubes that allow each node to sample a logarithmic number of nodes uniformly at random in O(log log n) communication rounds. These primitives are specific to overlay networks and their optimal runtime represents an exponential improvement over known techniques. Our results have a wide range of applications, for example in the area of scalable and robust peer-to-peer systems.

Erweichungszonen beim Widerstandspunktschweißen von DP- und CP-Stählen – Analyse und Bewertung der Verbindungen im Hinblick auf die Tragfähigkeit

Challenge Accepted! - The Impcat of Goal Achievement on Subsequent User Effort and Implications of a Goal's Difficulty - von Rechenberg, Tobias; Gutt, Dominik (Proceedings of the 24th Conference on Information Systems (ECIS), Istanbul)
We empirically investigate the impact of successful goal achievement on future effort to attain the next goal in a recurring goal framework. We use data from a popular German Question & Answer community where goals are represented in the form of badges. In particular, our analysis of this data hinges on the fact, that in this Question & Answer community, badges in a hierarchical badge system are in-creasingly challenging to attain up to a certain badge. After this certain badge, the difficulty level sud-denly drops and remains constant throughout up to the last badge in the hierarchy. Our findings indi-cate that after successful badge achievement users increase their subsequent effort to attain the next badge, but only as long as badges represent a challenge to the user. According to our analysis, we identify self-learning to be the key driver of this behavior.

Imprecise Matching of Requirements Specifications for Software Services Using Fuzzy Logic - Platenius, Marie C.; Shaker, Ammar; Becker, Matthias; Hullermeier, Eyke; Schäfer, Wilhelm (IEEE Transactions on Software Engineering)

Ontologie-Erstellung mittels Text-Mining aus App-Marktplätzen am Beispiel des Google Marketplace - Heck, Eduard

Innovationsmanagement an Hochschulen: Maßnahmen zur Unterstützung der Digitalisierung von Studium und Lehre - Budde, Jannica; Oevel, Gudrun (INFORMATIK 2016)

Der Ton macht die Musik. Digitalisierung von Forschungsprozessen nicht nur in der Musikwissenschaft - Oevel, Gudrun ("Ei, dem alten Herrn zoll' ich Achtung gern'". Festschrift für Joachim Veit zum 60. Geburtstag)

G´schichten aus dem Rechnerwald: Sieben auf einen Streich - Oevel, Gudrun (Kooperation von Rechenzentren. Festkolloquium für Gerhard Schneider zum 60. Geburtstag)

Ontologie-basierte Extraktion funktionaler Softwareanforderungen am Fallbeispiel mobiler Kommunikationsapplikationen - Schwentker, Christoph

On-The-Fly Construction of Provably Correct Service Compositions - Templates and Proofs - Walther, Sven; Wehrheim, Heike (Science of Computer Programming)
Today, service compositions often need to be assembled or changed on-the-fly, which leaves only little time for quality assurance. Moreover, quality assurance is complicated by service providers only giving information on their services in terms of domain specific concepts with only limited semantic meaning.In this paper, we propose a method for constructing service compositions based on pre-verified templates. Templates, given as workflow descriptions, are typed over a (domain-independent) template ontology defining concepts and predicates. Their meaning is defined by an abstract semantics, leaving the specific meaning of ontology concepts open, however, only up to given ontology rules. Templates are proven correct using a Hoare-style proof calculus, extended by a specific rule for service calls. Construction of service compositions amounts to instantiation of templates with domain-specific services. Correctness of an instantiation can then simply be checked by verifying that the domain ontology (a) adheres to the rules of the template ontology, and (b) fulfills the constraints of the employed template.

On- and Off-Topic Classification and Semantic Annotation of User-Generated Software Requirements - Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2016 Conference on Empirical Methods in Natural Language Processing (EMNLP))
Users prefer natural language software requirements because of their usability and accessibility. When they describe their wishes for software development, they often provide off-topic information. We therefore present an automated approach for identifying and semantically annotating the on-topic parts of the given descriptions. It is designed to support requirement engineers in the requirement elicitation process on detecting and analyzing requirements in user-generated content. Since no lexical resources with domain-specific information about requirements are available, we created a corpus of requirements written in controlled language by instructed users and uncontrolled language by uninstructed users. We annotated these requirements regarding predicate-argument structures, conditions, priorities, motivations and semantic roles and used this information to train classifiers for information extraction purposes. The approach achieves an accuracy of 92% for the on- and off-topic classification task and an F1-measure of 72% for the semantic annotation.

The Game of Reciprocation Habits - Polevoy, Gleb; de Weerdt, M.M.; Jonker, C.M. (Proceedings of the 2016 European Conference on Artificial Intelligence)
Keywords: agents; action; repeated reciprocation; fixed; floating; network; Nash equilibrium; social welfare; price of anarchy; price of stability; convex combination

The Convergence of Reciprocation - Polevoy, Gleb; de Weerdt, Mathijs; Jonker, Catholijn (Proceedings of the 2016 International Conference on Autonomous Agents and Multiagent Systems)
Keywords: agent's influence; behavior; convergence; perron-frobenius; reciprocal interaction; repeated reciprocation

On the Parameterized Parallel Complexity and the Vertex Cover Problem - Abu-Khzam, Faisal N.; Li, Shouwei; Markarian, Christine; Meyer auf der Heide, Friedhelm; Podlipyan, Pavel (Proceedings of the 10th International Conference on Combinatorial Optimization and Applications (COCOA))
Efficiently parallelizable parameterized problems have been classified as being either in the class FPP (fixed-parameter parallelizable) or the class PNC (parameterized analog of NC), which contains FPP as a subclass. In this paper, we propose a more restrictive class of parallelizable parameterized problems called fixed-parameter parallel-tractable (FPPT). For a problem to be in FPPT, it should possess an efficient parallel algorithm not only from a theoretical standpoint but in practice as well. The primary distinction between FPPT and FPP is the parallel processor utilization, which is bounded by a polynomial function in the case of FPPT. We initiate the study of FPPT with the well-known k-vertex cover problem. In particular, we present a parallel algorithm that outperforms the best known parallel algorithm for this problem: using O(m) instead of O(n2) parallel processors, the running time improves from 4logn+O(kk) to O(k⋅log3n), where m is the number of edges, n is the number of vertices of the input graph, and k is an upper bound of the size of the sought vertex cover. We also note that a few P-complete problems fall into FPPT including the monotone circuit value problem (MCV) when the underlying graphs are bounded by a constant Euler genus.

Eigenkapitalverzehr und Substanzbesteuerung deutscher Unternehmen durch eine Vermögensteuer – eine empirische Analyse - Hoppe, Thomas; Maiterth, Ralf; Sureth-Sloane, Caren (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung)
Die (Wieder-)Einführung einer Vermögensteuer ist in den vergangenen Jahren erneut in den Fokus der politischen Diskussion gerückt. Der vorliegende Beitrag vermittelt einen Eindruck von den Belastungswirkungen, die aus der Umsetzung von aktuell vorliegenden Besteuerungskonzepten resultieren würden. Auf der Basis von realen Jahresabschlussdaten wird eine mehrperiodige Veranlagungssimulation durchgeführt, die insbesondere ermöglicht, den zu erwartenden Eigenkapitalverzehr sowie den Anstieg der Steuerbelastung für die betrachtete Stichprobe zu quantifizieren. Von besonderem Interesse sind hierbei Unternehmen, deren laufende Erträge nicht ausreichen, um die Belastungen durch die Vermögensteuer zu tragen und damit einem Substanzverzehr ausgesetzt sind. Es zeigt sich, dass etwa die Hälfte der Unternehmen im Untersuchungszeitraum von sechs Jahren in mindestens einem Jahr einen Substanzverzehr erfährt. Der Vermögensteuer kommt somit keinesfalls der vielfach postulierte Charakter einer eher mäßig belastenden und im Wesentlichen substanzverschonenden Steuer zu. Zusatzbelastungen von knapp 100 bis zu 300 % der Ertragsteuerlast sind keine Seltenheit und veranschaulichen das Gefährdungspotenzial dieser Steuer für den Wirtschaftsstandort Deutschland.
Keywords: Steuerbelastung; Substanzbesteuerung; Ungleiche Vermögensverteilung; Veranlagungssimulation; Vermögensteuer

40 issues of ICAME News/ICAME Journal - Mindt, Ilka (ICAME Journal 40)

An interview with Joybrato Mukherjee, the Chair oft he ICAME Board - Kytö, Merja; Stenström, Anna-Brita; Mindt, Ilka (ICAME Journal 40)

Tax Loss Offset Restrictions and Biased Perceptions of Risky Investments - Mehrmann, Annika; Sureth-Sloane, Caren

The diachronic development of 'COME TO V' - Mindt, Ilka (Silesian Studies in English 2015)

On the Design and Defense of Networks - An Experimental Investigation - Endres, Angelika Elfriede

On the abuse of market power - an economic perspective of Microsoft antitrust cases - Pehlivan, Muhammet

Introduction to the Special Issue on SPAA 2014 (Transactions on Parallel Computing (TOPC))

Das Eisenacher Regulativ und das Wiesbadener Programm. Die Diskussion um den evangelischen Kirchenbau und die Wiesbadener Kirchenbauten des 19. Jahrhunderts - Seng, Eva- Maria (Das Wiesbadener Programm und seine Bedeutung für den Kirchenbau. Zum Gedächtnis an Prof. Dr. Gottfried Kiesow)

Palmanova, eine Idealstadt im Friaul - Seng, Eva- Maria (ZIBALDONE. Zeitschrift für italienische Kultur der Gegenwart, No. 60, Herbst 2015)

Patrimoine culturel immatériel: plaidoyer pour une vision globale du patrimione culturel - Seng, Eva- Maria (Mutations de la culture patrimoniale)

Aus Fehlern lernen? Was kann man bei der Vergabe des Titels immaterielles Kulturerbe aus den Erfahrungen mit dem materiellen Kulturerbe ableiten und verbessern? - Seng, Eva- Maria (Altes Zeug: Beiträge zur Diskussion zum nachhaltigen Kulturgutschutz)

Confidentiality and Authenticity for Distributed Version Control Systems - A Mercurial Extension - Lass, Michael; Leibenger, Dominik; Sorge, Christoph (Proc. 41st Conference on Local Computer Networks (LCN))
Version Control Systems (VCS) are a valuable tool for software development and document management. Both client/server and distributed (Peer-to-Peer) models exist, with the latter (e.g., Git and Mercurial) becoming increasingly popular. Their distributed nature introduces complications, especially concerning security: it is hard to control the dissemination of contents stored in distributed VCS as they rely on replication of complete repositories to any involved user. We overcome this issue by designing and implementing a concept for cryptography-enforced access control which is transparent to the user. Use of field-tested schemes (end-to-end encryption, digital signatures) allows for strong security, while adoption of convergent encryption and content-defined chunking retains storage efficiency. The concept is seamlessly integrated into Mercurial---respecting its distributed storage concept---to ensure practical usability and compatibility to existing deployments.
Keywords: access control; distributed version control systems; mercurial; peer-to-peer; convergent encryption; confidentiality; authenticity

Imprecise Matching of Requirements Specifications for Software Services using Fuzzy Logic - Platenius, Marie Christin; Shaker, Ammar; Becker, Matthias; Hüllermeier, Eyke; Schäfer, Wilhelm (IEEE Transactions on Software Engineering (TSE), presented at ICSE 2017)
Today, software components are provided by global markets in the form of services. In order to optimally satisfy service requesters and service providers, adequate techniques for automatic service matching are needed. However, a requester’s requirements may be vague and the information available about a provided service may be incomplete. As a consequence, fuzziness is induced into the matching procedure. The contribution of this paper is the development of a systematic matching procedure that leverages concepts and techniques from fuzzy logic and possibility theory based on our formal distinction between different sources and types of fuzziness in the context of service matching. In contrast to existing methods, our approach is able to deal with imprecision and incompleteness in service specifications and to inform users about the extent of induced fuzziness in order to improve the user’s decision-making. We demonstrate our approach on the example of specifications for service reputation based on ratings given by previous users. Our evaluation based on real service ratings shows the utility and applicability of our approach.

Literaturwissenschaft - Eke, Norbert Otto; Allkemper, Alo

Das Politische und die Politik im Vormärz

How to Complete Customer Requirements: Using Concept Expansion for Requirement Refinement - Geierhos, Michaela; Bäumer, Frederik Simon (Proceedings of the 21st International Conference on Applications of Natural Language to Information Systems (NLDB))
One purpose of requirement refinement is that higher-level requirements have to be translated to something usable by developers. Since customer requirements are often written in natural language by end users, they lack precision, completeness and consistency. Although user stories are often used in the requirement elicitation process in order to describe the possibilities how to interact with the software, there is always something unspoken. Here, we present techniques how to automatically refine vague software descriptions. Thus, we can bridge the gap by first revising natural language utterances from higher-level to more detailed customer requirements, before functionality matters. We therefore focus on the resolution of semantically incomplete user-generated sentences (i.e. non-instantiated arguments of predicates) and provide ontology-based gap-filling suggestions how to complete unverbalized information in the user’s demand.
Keywords: Requirement refinement; Concept expansion; Ontology-based instantiation of predicate-argument structure

Strategic Network Disruption and Defense - Hoyer, Britta; De Jaegher, Kris (Journal of Public Economic Theory)
We study a game between a network designer, who uses costly links to connect nodes in a network, and a network disruptor who tries to disrupt the resulting network as much as possible by deleting either nodes or links. For low linking costs networks with all nodes in symmetric positions are a best response of the designer under both link deletion and node deletion. For high linking costs the designer builds a star network under link deletion, but for node deletion excludes some nodes from the network to build a smaller but stronger network. For intermediate linking costs the designer again builds a symmetric network under node deletion but a star‐like network with weak spots under link deletion.

Herausforderungen im Umgang mit unvollständigen Softwareanforderungen durch Semantic Role Labeling - Reckhorn, Lena

‚Reden‘ über Dichtung. Poetik-Vorlesungen und Poetik-Dozenturen im literarischen Feld - Eke, Norbert Otto (Text + Kritik X/16, Sonderband: Poetik des Gegenwartsromans. Hg. von Nadine J. Schmidt und Kalina Kupczyńska)

„Um so etwas bekümmre ich mich nicht“. Grabbe und die Moral - Eke, Norbert Otto (Text + Kritik IX/16)

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, Dirk Florian; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)

By-product mutualism and the ambiguous effects of harsher environments – A game-theoretic model - De Jaegher, Kris; Hoyer, Britta (Journal of Theoretical Biology)
We construct two-player two-strategy game-theoretic models of by-product mutualism, where our focus lies on the way in which the probability of cooperation among players is affected by the degree of adversity facing the players. In our first model, cooperation consists of the production of a public good, and adversity is linked to the degree of complementarity of the players׳ efforts in producing the public good. In our second model, cooperation consists of the defense of a public, and/or a private good with by-product benefits, and adversity is measured by the number of random attacks (e.g., by a predator) facing the players. In both of these models, our analysis confirms the existence of the so-called boomerang effect, which states that in a harsh environment, the individual player has few incentives to unilaterally defect in a situation of joint cooperation. Focusing on such an effect in isolation leads to the "common-enemy" hypothesis that a larger degree of adversity increases the probability of cooperation. Yet, we also find that a sucker effect may simultaneously exist, which says that in a harsh environment, the individual player has few incentives to unilaterally cooperate in a situation of joint defection. Looked at in isolation, the sucker effect leads to the competing hypothesis that a larger degree of adversity decreases the probability of cooperation. Our analysis predicts circumstances in which the "common enemy" hypothesis prevails, and circumstances in which the competing hypothesis prevails.

Der Reisende Müller - Eke, Norbert Otto (Reiseliteratur der DDR. Bestandsaufnahme und Modellanalysen)

Grabbes und Büchners Zeithorizonte - Eke, Norbert Otto (Innovation des Dramas im Vormärz: Grabbe und Büchner)

Das Politische und die Politik im Vormärz - Eke, Norbert Otto; Füllner, Bernd (Das Politische und die Politik im Vormärz)

„Aus wenigen Phonemen erstehen Welten in der Vorstellung des Zuschauers.“ Werner Fritsch: Autor, Regisseur – Visionär - Eke, Norbert Otto (Werner Fritsch: Nofretete / Das Rad des Glücks / Mutter Sprache)

„Zeit ist geblieben / Zeit ohne Zeit“. Chronotopische Konstruktionen im Werk Herta Müllers - Eke, Norbert Otto (Herta Müller und das Glitzern im Satz. Eine Annäherung an Gegenwartsliteratur)

„Wir kommen/Ins Heilige hinein/Noch auch“. Zum Religiösen als Paradigma der deutschsprachigen Gegenwartsliteratur - Eke, Norbert Otto (Kultur und Religion. Eine interdisziplinäre Bestandsaufnahme)

Das Junge Deutschland und der Europagedanke - Eke, Norbert Otto (Europa im Vormärz. Eine transnationale Spurensuche)

„Nischt! Immermannscher Wust!“ Karl Immermann und das Theater im Vormärz - Eke, Norbert Otto (Immermanns theatralische Sendung. Karl Leberecht Immermanns Jahre als Dramatiker und Theaterintendant in Düsseldorf (1827-1837))

Drei im gestimmten Raum. Lea Singers Verdis letzte Versuchung - Eke, Norbert Otto („Ei, dem alten Herrn zoll ich Achtung gern“. Festschrift für Joachim Veit zum 60. Geburtstag)
Angaben zur Herausgeberschaft: Hg. von Kristina Richts und Peter Stadler für den virtuellen Forschungsverbund Edirom

Goals as Reference Points: Empirical Evidence from a Virtual Reward System - von Rechenberg, Tobias; Gutt, Dominik; Kundisch, Dennis (Decision Analysis)
Heath et al. (1999) propose a prospect theory model for goal behavior. Their analytical model is based on the assumption that goals inherit the main properties of the prospect theory value function, i.e., reference point dependence, loss aversion, and diminishing sensitivity. We investigate whether these main properties transfer to goal behavior in the field. We take user activity data from a gamified Question & Answer community and analyze how users adjust their contribution behavior in the days surrounding goal achievement, where goals are represented by badges. We find that users gradually increase their performance in the days prior to earning a badge, with performance peaking on the day of the promotion. In subsequent days, user performance gradually diminishes again, with the decline being strongest on the day immediately following the badge achievement. These findings reflect the characteristic S-shape of the prospect theory value function which is convex below the reference point and concave above it. Employing the target-based approach, we can interpret the value function as a cumulative density function of a unimodal probability distribution. Our results suggest that it is more likely that active members of the community focus on the next badge relative to the status already achieved, as their next goal and are less likely to focus on more remote (higher-ranked) badges. Our results thus support the transferability of the main properties of the prospect theory value function to goal behavior in the field and suggest a distinct shape of the value function around goals.

Gefälschte Online Bewertungen - Literaturüberblick - Sassenberg, Tristan

Valentin, Thomas - Eke, Norbert Otto (Neue Deutsche Biographie Bd. 26)

Supporting Additive Manufacturing by Augmented Reality - Gräßler, Iris; Taplick, Patrick (6th International Conference on Additive Technologies iCAT 2016)

Szenario-basierte Analyse von Anforderungen im Produktentwicklungsprozess - Gräßler, Iris; Scholle, Philipp (Design for X, 27. Dfx-Symposium)

Eleven Potentials for mechatronic V-model - Gräßler, Iris; Hentze, Julian; Yang, Xiaojun (Production Engineering and Management, 6th International Conference, Band 01/2016)

Identification of indirect influences under time-variant impacts in scenario technique for foresight - Gräßler, Iris; Scholle, Philipp (R&D Management Conference 2016)

Enhancing Systems Engineering by Scenario-based Anticipation of Future Developments - Gräßler, Iris; Hentze, Julian; Scholle, Philipp (SoSe2016, 11th International Conference on System of Systems Engineering Conference)

Educational Learning Factory of a holistic Product Creation Process; 6th CLF - 6th CIRP Conference on Learning Factories

Interdisciplinary development of production systems using Systems Engineering - Gräßler, Iris; Yang, Xiaojun (26th CIRP Design Conference)

Enhancing scenario technique by time-variant impacts - Gräßler, Iris; Scholle, Philipp (DS 84, Proceedings of the DESIGN 2016 14th International Design Conference, Band 2)

VDI-Statusbericht: Digitale Chancen und Bedrohungen - Geschäftsmodelle für Industrie 4.0

Kapitel: Additive Fertigungsverfahren im Kontext von Industrie 4.0 - Klemp, Eric; Pottebaum, Jens (Handbuch Industrie 4.0: Produktion, Automatisierung und Logistik)

Assessing the accuracy of improved force-matched water models derived fromAb initiomolecular dynamics simulations - Köster, Andreas; Spura, Thomas; Rutkai, Gábor; Kessler, Jan; Wiebeler, Hendrik; Vrabec, Jadran; Kühne, Thomas D. (Journal of Computational Chemistry)